Perceived input control on digital platforms: a mixed-methods investigation of web-browser platforms. Issue 1 (2nd January 2021) - Croitor, Evgheni; Adam, Martin; Benlian, Alexander
ABSTRACT: Complementary products and services of third-party complementors have become one of the cornerstones for the success and sustainability of digital platforms. To understand how and why these complementors and their complements decide to contribute to digital platforms, Information Systems (IS) research has paid considerable attention to the effects of control modes on shaping platform governance. However, there is still a lack of understanding of the causal effects of a widely applied, yet under-examined control mode, namely input control (i.e. the set of mechanisms that screen and sort out complementors and their complements before entering the digital platform's ecosystem). In particular, extant literature has largely ignored the distinction between complementor-related and complement-related input control. Using a sequential mixed-methods approach, this paper first provides results of a quantitative study from a survey with 114 web-browser extension developers to investigate hypothesised relationships, then provides a qualitative study based on semi-structured interviews with 22 developers to confirm and complement the formerly found relationships. Both studies provide consistent support for the assertion that both complementor-related and complement-related input control negatively affects complementors' continuance intentions and that perceived usefulness and satisfaction mediate these effects. As such, our paper contributes to IS governance research primarily by (1) conceptually distinguishing between complementor-related and complement-related input control and (2) uncovering their distinct effects on critical complementor beliefs, attitudes and behavioural intentions. Moreover, our paper offers insights that can help platform providers to effectively manage their screening and gatekeeping processes for the success and sustainability of their digital platforms.